Repository managers: guidelines to meet H2020 requirements - Saraiva, Ricardo (2015)
Apresentação realizada em 23 outubro de 2015 no: National Workshop for Open Access: «Open Access to research publications & data», Nicosia, Chipre. Também acessível em: http://hdl.handle.net/10797/14460